Risk Assessment of Acute Upper Gastrointestinal Haemorrhage with Rockall Score In DMCH - Islam, Md Nazrul; Rahman, Md Sazedur; Kabir, Humayun; Huq, Zahirul; Amin, Robed; Azad, Khan Abul Kalam (Bangladesh Journal of Medicine, 2018)
Introduction: Rockall score is used for risk assessment in acute upper gastrointestinal haemorrhage for intervention and prediction for risk of rebleeding and mortality. Methods: This is a cross sectional hospital based observational study carried out among patients presented with haematemesis with or without melaena in the department of Medicine, Dhaka Medical College Hospital from April, 2013 to March 2014 in one hundred consecutive cases. Rockall score done before and after endoscpy. Results:Patients mean age found 45.12±14.9 years with 4:1 male to female ratio. Service holder were (26.0%) and 91.0% were married. Almost half (48.0%) was educated. Combined haematemesis and melaena was presenting feature in 62.0% patients among them 72.0% arrived in hospital within 24 hours of onset. Comorbidity was found in 42.0% cases and 13% took NSAID. Oesophageal varix was found in 25.0%. No death observed in 18% haematemesis patients, one died from melaena (1 of 5) but most died (4 out of 5) from combined haematemesis and melaena. All the 5 death occurred in 89% rebleeding cases. No death observed in 34% patients having pre endoscopic Rockall Score d” 2; as well as in 44% cases post endoscopic Rockall score d”5 score. Mean duration Hospital stay was 6.36±4.5 days. Conclusions: Rockall score is useful in predicting outcomes in acute upper gastrointestinal haemorrhage. Bangladesh J Medicine Jan 2018; 29(1) : 13-25